Association of Insulin, Metformin, and Statin with Mortality in Breast Cancer Patients - Choi, Mihong; Han, Jiyeon; Yang, Bo Ram; Jang, Myoung-jin; Kim, Miso; Lee, Dae-Won; Kim, Tae-Yong; Im, Seock-Ah; Lee, Han-Byoel; Moon, Hyeong-Gon; Han, Wonshik; Noh, Dong-Young; et al. (Cancer research and treatment, 2021)
Purpose This study investigated the association of insulin, metformin, and statin use with survival and whether the association was modified by the hormone receptor status of the tumor in patients with breast cancer.Materials and Methods We studied 7,452 patients who had undergone surgery for breast cancer at Seoul National University Hospital from 2008 to 2015 using the nationwide claims database. Exposure was defined as a recorded prescription of each drug within 12 months before the diagnosis of breast cancer.Results Patients with prior insulin or statin use were more likely to be older than 50 years at diagnosis and had a higher comorbidity index than those without it (p < 0.01 for both). The hazard ratio (HR) for death with insulin use was 5.7 (p < 0.01), and the effect was attenuated with both insulin and metformin exposure with an HR of 1.2 (p=0.60). In the subgroup analyses, a heightened risk of death with insulin was further prominent with an HR of 17.9 (p < 0.01) and was offset by co-administration of metformin with an HR of 1.3 (p=0.67) in patients with estrogen receptor (ER)–negative breast cancer. Statin use was associated with increased overall mortality only in patients with ER-positive breast cancer with HR for death of 1.5 (p=0.05).Conclusion Insulin or statin use before the diagnosis of breast cancer was associated with an increase in all-cause mortality. Subsequent analyses suggested that metformin or statin use may have been protective in patients with ER-negative disease, which warrants further studies.